Nature Experiences in Science Education in School: Review Featuring Learning Gains, Investments, and Costs in View of Embodied Cognition - Schilhab, Theresa (Frontiers in Education, 2021)
This review examines the didactic use of nature experiences in science education, in primary and secondary school (7–16 years) globally. From the perspective of embodied cognition the review explores the types of nature experiences used in science teaching. Focus is on returns when we invest in nature-based science learning, such as specific academic achievements in the form of long-term effects on learning and memory and how we maximize those returns. The review also addresses challenges and barriers, such as costs and labour involved when using nature experiences in science teaching. Initially, 3,659 articles were selected, with the initial screening leading to the inclusion of 159 studies. Of these articles, 34 studies forming the corpus in this review investigated the effect of using nature experiences as an intervention. These studies are divided into four themes: content understanding, environmental education, teaching scientific methods, and costs and challenges to teaching science outdoors. Informed by the perspective of embodied cognition, the review addresses the returns in terms of learning and academic achievements, the mode of action of the intervention, the investment, costs in the form of labour, challenges, and gaps in the theoretical underpinning of the field. Based on the review, using nature experiences in science education seems promising regarding increasing content knowledge, insight into science methodologies and pro-environmental behaviours. Interventions exploiting the schoolyard, school gardens, or nearby park areas are particularly promising due to the simultaneous strengthening of local engagement at low costs. However, using nature experiences as an alternative to traditional in-class teaching depends on profound didactic deliberations and preparations, which are difficult for the individual teacher to address single-handedly. The review also reveals an urgent need for research that thoroughly explores the connections between teaching practices and theoretical foundations to consolidate the field. To that end, it is noteworthy that a few studies also reported on prior pilot studies demonstrating the need for testing the entire design before conducting the actual research. Teachers seldom experience the opportunity to preview their teaching strategies before performing in front of their students.